Research on the Environment Assisted Fatigue Based on Flaw Tolerance Method. (2015) - Shen, R.; He, Y.B.; Cao, M.
Abstract: Shanghai Nuclear Engineering Research and Design Institute (SNERDI) have been involved in "Fatigue Evaluations Using Flaw Tolerance Methods to Consider Environmental Effects" task group (TG) under the WG Environmental Fatigue Evaluation Methods (WG EFEM) in 2012 founded by ASME section III committee which is intend to find alternative rules for fatigue assessments when considering primary loop water environment. EAF TG has researched a sample problem based on a heavy-walled primary loop stainless steel nozzle for light water reactor (LWR). The cumulative fatigue usage factor and Fen (Environmentally Assistant Fatigue Factor) value is determined by ASME Code Case N-792. Based on this, the fatigue crack growth is calculated according to the rules of ASME section XI non-mandatory appendix L. The crack depth at 1000 cycles and the cycles when the crack grow to 0.75 times of wall thickness is calculated for the axial and circumferential crack respectively. Moreover, the crack closure effect in the fatigue crack growth under PWR environment has been studied. The results of the two methods of Fen factor correction and flaw tolerance are compared and discussed.